Design and Synthesis of Waterborne Polyurethanes. Issue 18 (15th March 2018) - Kang, Soo‐Young; Ji, Zhaoxia; Tseng, Ling‐Fang; Turner, Sara A.; Villanueva, Dinara A.; Johnson, Rhiannon; Albano, Ariana; Langer, Robert
Abstract: Waterborne polyurethanes (WBPUs) have attracted increasing attention in a wide range of industrial applications because of their versatile properties as well as ecofriendly nature. Although extensive research has been carried out on WBPU synthesis, the roles of some of the key synthesis components remain unclear. In this study, through systematically controlling and fine tuning the precursor compositions and reaction conditions, over 300 WBPUs are synthesized. This research enables the roles of several key components that govern WBPU physicochemical properties and ultimately the potential WBPU applications to be identified. Using hair styling as an example, it is demonstrated that only the WBPUs with an optimal range of properties (e.g., Young's modulus >150 MPa, elongation at break: 15–300%, moisture uptake <10%) can achieve strong styling performance. To further improve the natural‐feel sensory benefits in the final styling products, a number of fatty acids with different carbon chain lengths or unsaturation levels are incorporated into WBPUs. Among the ten fatty acids studied, linoleic acid is identified as the most preferred additive. Both in vitro and in vivo testing demonstrate that WBPUs with optimal properties are promising materials for developing strong, long‐lasting styling products with natural feel. Abstract : Through the synthesis of over 300 waterborne polyurethane (WBPU) materials, the roles of the key components that govern WBPU physicochemical properties are identified. Using hair styling as an example, it is demonstrated that only the WBPUs with Young's modulus >150 MPa, elongation at break of 15–300%, and moisture uptake <10% can achieve strong styling performance.